Ubc9 Attenuates Myocardial Ischemic Injury Through Accelerating Autophagic Flux - Xiao, Qing; Chen, Xiu-Hui; Jiang, Ru-Chao; Chen, Sheng-Ying; Chen, Kai-Feng; Zhu, Xiang; Zhang, Xiao-ling; Huang, Jun-jun; Qin, Yuan; Zhang, Gui-Ping; Yi, Quan; Luo, Jian-dong (Frontiers in Pharmacology, 2020)
Aims: SUMOylation is a post-translational modification that plays a crucial role in the cellular stress response. We aimed to demonstrate whether and how the SUMO E2 conjugation enzyme Ubc9 affects acute myocardial ischemic (MI) injury. Methods and Results: Adenovirus expressing Ubc9 was administrated by multipoint injection in the border zone of heart immediately after MI in C57BL/6 mice. Neonatal rat cardiomyocytes (NRCMs) were also infected, and oxygen and glucose deprivation (OGD) followed. In vivo, Ubc9 adenovirus-injected mice showed decreased cardiomyocyte apoptosis, reduced myocardial fibrosis, and improved cardiac function post-MI. In vitro, overexpression of Ubc9 decreased cardiomyocyte apoptosis, whereas silence of Ubc9 showed the opposite results during OGD. We next found that Ubc9 significantly decreased the accumulation of autophagy marker p62/SQSTM, while the LC3 II level hardly changed. When in the presence of bafilomycin A1 (BAF), the Ubc9 adenovirus plus OGD group presented a higher level of LC3 II and GFP-LC3 puncta than the OGD group. Moreover, the Ubc9 adenovirus group displayed increased numbers of yellow plus red puncta and a rising ratio of red to yellow puncta on the mRFP-GFP-LC3 fluorescence assay, indicating that Ubc9 induces an acceleration of autophagic flux from activation to degradation. Mechanistically, Ubc9 upregulated SUMOylation of the core proteins Vps34 and Beclin1 in the class III phosphatidylinositol 3-kinase (PI3K-III) complexes, and boosted the protein assembly of PI3K-III complex I and II under OGD. Moreover, the colocalization of Vps34 with autophagosome marker LC3 or lysosome marker Lamp1 was augmented after Ubc9 overexpression, indicating a positive effect of Ubc9-boosted protein assembly of the PI3K-III complexes on autophagic flux enhancement. Conclusions: We uncovered a novel role of Ubc9 in protecting cardiomyocytes from ischemic stress via Ubc9-induced SUMOylation, leading to increased PI3K-III complex assembly and autophagy-positioning. These findings may indicate a potential therapeutic target, Ubc9, for treatment of myocardial ischemia.